Independent Curriculum Management Through Developing Teaching Modules on Style Materials - Lina Novita; Stella Talitha; Rohimah Rohimah; Fitri Siti Sundari; Ratih Purnamasari (STAI Hubbulwathan Duri, 2024)
Educational achievement in Education for Sustainable Development (hereafter, EfSD) demands fair and equitable education. This condition gives rise to various preparations that must be taken into account by teaching staff through program plans and strategies designed to achieve the quality of education as regulated in the curriculum. The aim of the research is to examine the conditions for implementing EfSD in elementary schools through the management of learning modules. The research uses the Research and Development or RD method with the ADDIE model. The research begins with an analysis stage consisting of analysis of problems, needs and curriculum, teachers and students. The design stage takes the form of resource management and management of material aspects through the development of independent curriculum teaching modules. At this stage, a validation test was carried out by material experts and practitioners which resulted in an average of 94.48%. Then the implementation or trial phase was limited to 10 students, the test was extensive on 22 grade 4 students. The evaluation stage aims to determine the suitability of the independent curriculum teaching module product for use in schools. The test results showed that student responses were limited to 87.87% and broadly 93.24%. It can be concluded that the development of teaching modules attracts students to learn according to their characteristics, skills and interests.